Discussing health while seeking community: A descriptive study of celiac disease on TikTok. Issue 1 (March 2023) - Jaime, Christie; Samuel, Lalitha; Fera, Joseph; Basch, Corey H.
Background : For individuals suffering from chronic disease, more than being an information source for health information, social media serves as a dynamic forum for shared goals, emotional and practical support through the sharing of lived experiences.Aim: This study envisaged a content analysis of the 100 most widely-viewed English language videos related to celiac disease posted on TikTok.Methods: TikTok was searched using the hashtag #celiacdisease. This search term was chosen as it represented the broadest summation of the desired topic with the most views (80 million) of any related hashtag. The first 100 English language videos were selected. The video content was analyzed against predetermined descriptive categories, deductively derived content related to facts about celiac disease from a reliable source, and inductive content categories derived during the coding process.Results : The 100 videos included in this study received a total of 44, 056, 600 likes. The average number of likes across all videos was 440, 566 with a standard deviation of 656, 642.06. Two of the three categories were present in a majority (>50) of the videos. They were practical information on diet therapy management (n = 63) and challenges in managing celiac disease (n = 73). In both instances, videos featuring this content also garnered a majority of the likes, 74.18% and 82.9% respectively. Independent one-tailed t-tests (α = .05) returned significant results for the diagnosis-related information (p = .0390) and practical information in diet therapy management (p = .0358) categories. On average, videos that included diagnosis-related information received more likes than those that did not: 672, 983.33 vs. 340, 958.57. Similarly, the average number of likes was significantly higher for videos that included practical information on diet therapy management (518, 715.87) vs. those that did not (307, 500).Conclusions : This study further confirms the growing trend of people using social media to discuss health issues in a way that is free and easily accessible among communities with shared experiences. The long-term effects of using personal narratives as credible sources of behavioral change for health, medical, or professional resources can be further investigated.